Promoting oral interaction in large groups through task-based learning (2005)
This research project attempts to show the way a group of five teachers used task-based learning with a group of 50 seventh graders to improve oral interaction. The students belonged to Isabel II School. They took an active part in the implementation of tasks and were asked to answer two questionnaires. Some English classes were observed and recorded; finally, an evaluation was taken by students to test their improvement. Key words: Task-based learning, oral interaction, large groups, high school English teaching Este proyecto de investigación trata de mostrar la forma como un grupo de cinco profesoras usaron el método de aprendizaje basado en tareas con un grupo de 50 estudiantes del grado séptimo, con el fin de mejorar la interacción oral. Los estudiantes pertenecían al Colegio Isabel II y fueron parte activa en la implementación de las tareas. Respondieron dos cuestionarios, se les observó y se grabaron en video algunas clases; finalmente, se hizo una evaluación para poner a prueba el avance de los estudiantes. Palabras claves: Aprendizaje basado en tareas, interacción oral, grupos numerosos, enseñanza del Inglés en secundaria.